Predictors of depression in asthma patients in an Indian referral hospital - Anushka Kataria; Jefferson Daniel; Barney Isaac; Balamugesh Thangakunam; Jesson Paulson Illimoottil; Reka Karuppusami; Devasahayam J. Christopher (PLoS ONE, 2026)
Background Asthma has been shown to have a significant association with the diagnoses of mental health disorders, including depression; however, information from India is scarce. Objectives The study aims to estimate the prevalence of depression in asthma patients and identify associated risk factors. Methods A total of 248 participants aged 18 and above who presented to the pulmonary medicine outpatient clinic of the Christian Medical College, Vellore, Tamil Nadu, India, were recruited. Socio-demographic and clinical details, including treatment compliance were collected, and inhaler technique was assessed. Asthma control was measured by the Asthma Control Test (ACT) and the quality of life by Asthma Quality of Life Questionnaire (AQLQ). The Patient Health Questionnaire-9 (PHQ-9) was used to screen for depression. Logistic regression was used to determine the risk factors for depression. Results Out of the 248 participants, 24.6% screened positive for depression. Asthma control was worse (ACT 19.07 ± 4.87 vs 21.93 ± 3.66; p < 0.001) and quality of life was poorer (AQLQ 5.53 ± 0.72 vs 6.06 ± 0.63; p < 0.001) in those with depression. There was a low negative correlation (ρ = −0.332, P < 0.001) between ACT score and PHQ-9 score and a moderate negative correlation (ρ = −0.451, P < 0.001) between AQLQ score and PHQ-9 score. Univariate logistic regression analysis showed six independent factors associated with depression: female gender (OR 1.87), presence of one or more comorbidities (OR 2.10), incorrect inhaler technique (OR 3.59), poor compliance with inhaled corticosteroids (ICS) (OR 2.30), poorly controlled asthma (ACT) (OR 2.92) and lower AQLQ score (OR = 0.32). Multivariate logistic regression analysis revealed that the AQLQ was the only independent risk factor for depression (OR 0.27, P = 0.001). Conclusion Adult asthma patients in this Indian cohort showed a high prevalence of depression. The study highlights key risk factors for depression in asthma and reiterates the need to screen asthma patients for depression.